Construction of hollow structure cobalt iron selenide polyhedrons for efficient hydrogen evolution reaction. (25th August 2020) - Xue, Yanqin; Wang, Xianchao; Zhu, Min; Yan, Qing; Zhu, Kai; Cheng, Kui; Ye, Ke; Yan, Jun; Cao, Dianxue; Wang, Guiling
Summary: The development of highly active, robust and cost‐effective noble metal‐free electrocatalysts for hydrogen evolution reaction (HER) in alkaline solution remains a severe challenge. In this work, a hollow structure CoSe2 ‐FeSe2 heterojunction electrocatalyst (denoted by "(Co, Fe)Se2 ") was designed by a simple anion exchange reaction and selenization. Benefiting from the unique hollow structure, the (Co, Fe)Se2 catalyst accelerates diffusion of electrolyte, besides, the CoSe2 ‐FeSe2 heterojunction could provide rapid interfacial charge transportation and more active sites for the HER reaction. The (Co, Fe)Se2 electrode material exhibits good performance for HER in 1 M KOH electrolyte. It needs an overpotential of 124 mV to obtain a current density of 10 mA cm −2, and the Tafel slope is 65 mV dec −1 . Besides, (Co, Fe)Se2 has a smaller charge transfer resistance compared with CoSe2 . At the same time, it has relatively large electrochemical active surface area due to the porosity. Most importantly, the (Co, Fe)Se2 electrode displays good stability in alkaline conditions for 15 hours, the linear sweep voltammetry curves are almost coincident before and after 1000 cycles, the overpotential with current density of 10 mA cm −2 increased by only 9.76% after 5000 cycles of CV. It shows great application potential in HER.